Spatial Patterns and Environmental Influences on Soil Surface Collembola in Forest and Non-Forest Ecosystems - Haneda, Noor Farikhah; Priyanto; Hamdani, Muhammad (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Forests are one of the ecosystems with different habitat characteristics for certain species. The transition from forest to non-forest will affect the ecosystem and its resident species. The study aims to determine the presence of soil surface Collembola within various ecosystems, identify the types of soil surface Collembola present and their locations, analyze the impact of environmental conditions on their distribution, and identify the association between soil surface Collembola and Acari. The field procedures comprise the setup of litter traps, litter harvesting and extraction, measurement of environmental factors, and identification of soil surfaces in Collembola and Acari. Collembula is found in oil palm plantations. A total of 1,618 individuals were found in all ecosystem types, including 13 genera and 6 families: Cyphoderidae, Entomobryidae, Isotomidae, Oncopoduridae, Paronellidae, and Dicyrtomidae, along with 2 orders, Entomobyromorpha and Symphypleona, which showed grouped patterns in each ecosystem types. Several environmental factors, both biotic and abiotic,strongly influence the soilsurface of Collembola. From all ecosystem types, only secondary forest ecosystems lack an association between soil surface Collembola and Acari.